Omicron SARS-CoV-2 variant of concern: A review on its transmissibility, immune evasion, reinfection, and severity. Issue 19 (13th May 2022) - Mohsin, Md; Mahmud, Sultan
Abstract : Abstract: Omicron, the new Covid-19 variant, has already become dominant in many countries and is spreading at an unprecedented speed. The objective of this study was to review the existing literature on Omicron's transmissibility, immune evasion, reinfection, and severity. A literature search was performed using "PubMed, " "Web of Science, " "Scopus, " "ScienceDirect, " "Google Scholar, " "medRxiv, " and "bioRxiv." Data were extracted from articles that reported at least one of the following: transmissibility, immune evasion, reinfection, and severity related to Omicron. We found that Omicron spread faster than any other variant. This higher transmissibility can be ascribed to its extraordinary ability to evade the immunity developed by both vaccination and previous infections. However, we found that infections by Omicron were significantly less severe than those caused by Delta and other previous variants. We observed a significantly lower incidence of hospitalization, intensive care unit admission, and mechanical ventilator use in Omicron infections than in Delta or other variants. A substantially shorter median hospital stay and lower fatality rate were also observed in the Omicron infections. Despite Omicron's higher potential to evade immunity, vaccines and booster shots were found to be still significantly effective in protecting against severe Covid-19 infections. Omicrons may be less severe than other variants of concern. However, its immune evasiveness and rapid spread pose an enormous threat to the global healthcare system.